Perceptions of Tourism sector campaigns- Hidden Veracities - Varghese, Thresi; Said, Hiba Abduallah; Al Bloshi, Maryam Khalifa; Al Bloshi, Sohailah Khalifa; Al Karosi, Reem Mohammed (Advances in Social Sciences Research Journal, 2018)
The Ministry of Tourism is the government agency responsible for the tourism sector in the Sultanate of Oman. The main mission of the Ministry of Tourism is to promote Oman’s tourism sector regionally and globally by providing all the tourist information about its amazing locations and the heritage of the original Arabs. Natural tourist sites in Oman are mainly a source of attraction to tourists from around the world. This research aims to look at the tourism sector in Oman and to identify the strategies and techniques used by the Sultanate to promote tourism in Oman. We have collected data using primary sources through interviews with relevant authorities at the Ministry of Tourism, which have the authority to develop tourism sector in Oman. Moreover, we have collected information from tourist and various other sources such as websites, magazines, newspapers etc. One of the main finding of this study is that many respondents believes now-a –days tourism sector provides job opportunities to Omanis and moreover the tourism development is part of diversification strategy of Oman to enhance the income of the country.